2022
DOI: 10.1002/cb.2049
|View full text |Cite
|
Sign up to set email alerts
|

Do honesty‐nudges really work? A large‐scale field experiment in an insurance context

Abstract: Businesses want their customers to self-report information honestly. One increasingly popular way to stimulate desired behavior is by using nudge interventions. But can customers be nudged to self-report information more honestly? This is currently a debate in the literature, where empirical results are inconclusive. Building on related literature on nudges, we add to this debate with a controlled field experiment (N = 5704). We used data from actual customers making real decisions when they file claims online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…This is supported by empirical research, both in the lab and in the field, indicating that mitigating dishonest behavior through behavioral interventions alone, e.g. norm-nudges or defaults, is challenging [6,9,35,[50][51][52][53]. This is further augmented by theoretical arguments stressing that the nudgeability of individuals matters, which is often overlooked in existing research and deserves more scholarly attention moving forward [54].…”
Section: Challenges With and Promising Approaches For Nudging Honestymentioning
confidence: 79%
“…This is supported by empirical research, both in the lab and in the field, indicating that mitigating dishonest behavior through behavioral interventions alone, e.g. norm-nudges or defaults, is challenging [6,9,35,[50][51][52][53]. This is further augmented by theoretical arguments stressing that the nudgeability of individuals matters, which is often overlooked in existing research and deserves more scholarly attention moving forward [54].…”
Section: Challenges With and Promising Approaches For Nudging Honestymentioning
confidence: 79%
“…It is possible that different forms of expressing social norm commitment (e.g., signing instead of copying text) might produce stronger effects (see Skowronek, 2022 for a framework to improve honesty nudges). As previous studies did not find evidence for the effectiveness of commitment to oaths (Kristal et al, 2020;Koning et al, 2020;Martuza et al, 2022), it seems important to study the conditions under which such an intervention could reduce dishonesty.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, recent work has questioned the effectiveness of moral nudges. In a large field study, Martuza et al (2022) found that asking people to sign before submitting insurance claims, providing social norm messages, and even evoking solidarity had no effect on honesty. Taken together, these findings make the prediction that norm nudges should increase compliance less straightforward and worth examining.…”
Section: Behavior Prior To Receiving the Norm Nudge Requestmentioning
confidence: 99%